Corporate Social Responsibility, Ownership Structure and Firm Value: Evidence From Companies Listed on Indonesia Stock Exchange - Luluk Muhimatul IFADA; Maya INDRIASTUTI; Yulita SETIAWANTA (Communications of International Proceedings, 2021)
This study examined the effect of Corporate Social Responsibility on firm value and the effect of ownership structure in moderating the relationship of Corporate Social Responsibility on firm value. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2017 period. The samples were determined by using purposive sampling and resulted in a final sample of 105 listed companies. This study used multiple linear regression analysis through SPSS and indicated that corporate social responsibility positively affects firm value. Meanwhile, ownership structure has a negative effect on the relationship between corporate social responsibility and firm value.
Keywords: Corporate social responsibility; ownership structure; firm value